Association of severity of menstrual dysfunction with cardiometabolic risk markers among women with polycystic ovary syndrome - Xuelan Li; Jie Yang; Christophe Blockeel; Min Lin; Xiaoyan Tian; Haocun Wu; Yaqi Cao; Ling Deng; Xianli Zhou; Jinying Xie; Yunzhao Hu; Xin Chen (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Polycystic ovary syndrome (PCOS) is associated with a wide range of unfavorable cardiometabolic risk factors, including obesity, hypertension, insulin resistance, impaired glucose metabolism, dyslipidemia, and metabolic syndrome. Compared with women with regular menstrual cycles, women with a history of irregular menstrual periods have an increased unfavorable cardiometabolic risk. Recently, the association between the severity of oligomenorrhea and hyperinsulinemia and insulin resistance has been demonstrated. However, evidence linking the severity of menstrual cyclicity with cardiometabolic risk in PCOS women is scarce. Material and Methods This work was a prospective cross‐sectional study. A total of 154 women diagnosed with PCOS by the Rotterdam criteria were recruited from July 2021 to September 2022. PCOS women with eumenorrheic (eumeno group), oligomenorrhea (oligo group), and amenorrhea (ameno group) underwent history and physical examination, gonadal steroid hormone measurement, lipid profile, oral glucose tolerance test, and homeostasis model assessment of insulin resistance. Results A trend toward an increase in unfavorable cardiometabolic risk markers including obesity, hypertension, prevalence of insulin resistance, prediabetes, dyslipidemia, and metabolic syndrome was observed in the ameno group (n = 57) as compared with the eumeno (n = 24) or oligo group (n = 73). A higher prevalence of insulin resistance (odds ratio [OR]: 3.02; 95% confidence interval [CI]: 1.03–8.81) and prediabetes (OR: 3.94; 95% CI: 1.01–15.40) was observed in the ameno group than in the eumeno group, and a higher proportion of dyslipidemia (OR: 2.44; 95% CI: 1.16–5.15) was observed in the ameno group than in the oligo group in the binary logistic regression analysis after adjusting for confounding factors. Conclusions PCOS women with amenorrhea show a higher prevalence of insulin resistance, prediabetes, and dyslipidemia compared with those with oligomenorrhea or eumenorrhea. The severity of menstrual dysfunction could be used as a readily obtainable marker for the identification of PCOS women at greatest risk of cardiometabolic diseases.